Operating characteristics analysis and capacity configuration optimization of wind-solar-hydrogen hybrid multi-energy complementary system - Su, Wei; Li, Qi; Wang, Shuoshuo; Zheng, Wenjin; Bai, Zhang; Han, Yunyi; Yu, Zhenyue (Frontiers in Energy Research, 2023)
Wind and solar energy are the important renewable energy sources, while their inherent natures of random and intermittent also exert negative effect on the electrical grid connection. As one of multiple energy complementary route by adopting the electrolysis technology, the wind-solar-hydrogen hybrid system contributes to improving green power utilization and reducing its fluctuation. Therefore, the moving average method and the hybrid energy storage module are proposed, which can smooth the wind-solar power generation and enhance the system energy management. Moreover, the optimization of system capacity configuration and the sensitive analysis are implemented by the MATLAB program platform. The results indicate that the 10-minute grid-connected volatility is reduced by 38.7% based on the smoothing strategy, and the internal investment return rate can reach 13.67% when the electricity price is 0.04 /kWh. In addition, the annual coordinated power and cycle proportion of the hybrid energy storage module are 80.5% and 90%, respectively. The developed hybrid energy storage module can well meet the annual coordination requirements, and has lower levelized cost of electricity. This method provides reasonable reference for designing and optimizing the wind-solar-hydrogen complementary system.